Maternal hypoxia decreases capillary supply and increases metabolic inefficiency leading to divergence in myocardial oxygen supply and demand. - David Hauton; Abdullah Al-Shammari; Eamonn A Gaffney; Stuart Egginton (PLoS ONE)
Maternal hypoxia is associated with a decrease in left ventricular capillary density while cardiac performance is preserved, implying a mismatch between metabolism and diffusive exchange. We hypothesised this requires a switch in substrate metabolism to maximise efficiency of ATP production from limited oxygen availability. Rat pups from pregnant females exposed to hypoxia (FIO2=0.12) at days 10-20 of pregnancy were grown to adulthood and working hearts perfused ex vivo. 14C-labelled glucose and 3H-palmitate were provided as substrates and metabolism quantified from recovery of 14CO2 and 3H2O, respectively. Hearts of male offspring subjected to Maternal Hypoxia showed a 20% decrease in cardiac output (P<0.05), despite recording a 2-fold increase in glucose oxidation (P<0.01) and 2.5-fold increase (P<0.01) in palmitate oxidation. Addition of insulin to Maternal Hypoxic hearts, further increased glucose oxidation (P<0.01) and suppressed palmitate oxidation (P<0.05), suggesting preservation in insulin signalling in the heart. In vitro enzyme activity measurements showed that Maternal Hypoxia increased both total and the active component of cardiac pyruvate dehydrogenase (both P<0.01), although pyruvate dehydrogenase sensitivity to insulin was lost (NS), while citrate synthase activity declined by 30% (P<0.001) and acetyl-CoA carboxylase activity was unchanged by Maternal Hypoxia, indicating realignment of the metabolic machinery to optimise oxygen utilisation. Capillary density was quantified and oxygen diffusion characteristics examined, with calculated capillary domain area increased by 30% (P<0.001). Calculated metabolic efficiency decreased 4-fold (P<0.01) for Maternal Hypoxia hearts. Paradoxically, the decline in citrate synthase activity and increased metabolism suggest that the scope of individual mitochondria had declined, rendering the myocardium potentially more sensitive to metabolic stress. However, decreasing citrate synthase may be essential to preserve local PO2, minimising regions of hypoxia and hence maximising the area of myocardium able to preserve cardiac output following maternal hypoxia.